2013
DOI: 10.1080/07399332.2013.817411
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Antenatal Depression Among Jordanian Pregnant Women in Their Third Trimester

Abstract: Antenatal depression has not been well studied worldwide. The objective of this study was to identify the prevalence and predictors of antenatal depression among Jordanian pregnant women in their third trimester. A correlational design was used with a convenience sample of 218 Jordanian pregnant women. Data were collected using valid and reliable measures and were analyzed with regression. Fifty-seven percent of the women displayed symptoms of depression. Thirty-seven percent (34% adjusted) of the variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 28 publications
8
51
1
2
Order By: Relevance
“…This result was also found in several other studies [3336] that attribute this to a lower income being connected with a low level of education. In our study however the secondary education was found to be a protective factor (OR = 0.6, p  = 0.026) in the prenatal period in a multivariate analysis.…”
Section: Discussionsupporting
confidence: 87%
“…This result was also found in several other studies [3336] that attribute this to a lower income being connected with a low level of education. In our study however the secondary education was found to be a protective factor (OR = 0.6, p  = 0.026) in the prenatal period in a multivariate analysis.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to childhood abuse and abuse by intimate partner, maternal low educational attainment, 54,71 low socioeconomic status at the time of pregnancy, 54,71,72 lack of social support 73 and history of mental illness have been consistently identified as risk factors of antepartum and postpartum depression in the LAMICS. 74 For instance, Melo et al .…”
Section: Resultsmentioning
confidence: 99%
“…This has been studied and is reportedly less than in other populations e.g. pregnant women, patients with cancer or diabetes in Jordan [64][65][66] , Americans with CVD [54,67] , and Korean patients with CVD [46] . However, it may not be identified or acknowledged in Jordanian men.…”
Section: Discussionmentioning
confidence: 99%